Exploring the occupational therapy goal‐setting process with immigrant families of children with disabilities in the Australian context - Sarah Ninan Fenn; Natasha Jojo; Stephen Isbel; Claire Pearce (Australian Occupational Therapy Journal, 2026)
Abstract Introduction Collaborative relationship‐focussed practice centres on the relational aspects of co‐designing priorities and goals with individuals, collectives, and occupational therapists. To establish a relationship with immigrant families of children with disabilities, aligning the goals with their values and resources is essential. However, this is perceived as challenging, and there is a significant knowledge gap regarding how the goals are set in the occupational therapy process with immigrant families of children with disabilities. Objectives This study aimed to explore how immigrant families of children with disabilities contribute to and influence the occupational therapy goal‐setting process. Methods This study employed a qualitative methodology using constructivist grounded theory. This methodology enabled the researcher to inductively frame theory grounded in data in an area with limited literature. Consumer and Community Involvement Consumers and community members were not involved in the development or undertaking of this research. Results The occupational therapy goal‐setting process is complex and is influenced by families' culturally constructed wants, professional frameworks, and the demands of the broader system. Currently, the professional frameworks and demands of the system overshadow the occupational therapy goal‐setting process, compromising the focus on the overarching wants of immigrant families. Conclusion Collaborative relationship‐focussed occupational therapy practice involves shifting and centring the position of the immigrant families of children with disabilities. This can only be achieved by understanding and integrating families' wants into the occupational therapy process. Recognising and addressing their wants helps occupational therapists contextually position the family within their cultural, social, and political context.